PENERAPAN MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN KREATIVITAS SISWA SEKOLAH DASAR - Hawalya, Syahara; Adinda, Rahma; Habibi, M. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Creativity is one of the important skills that needs to be developed in elementary school students to face the challenges of 21st-century learning. However, low student creativity is still a problem in the learning process because learning tends to be teacher-centered, causing students to be less active in developing ideas and solving problems. One learning model that can be used to improve student creativity is Problem Based Learning (PBL). This study aims to analyze the effectiveness of the implementation of the Problem Based Learning (PBL) model in improving the creativity of elementary school students. This study used a literature review method by analyzing various scientific articles obtained from Google Scholar and GARUDA databases published between 2016–2026. The article selection process was carried out using the PRISMA flow diagram. Based on the search results, 31 articles were obtained and then selected until 10 articles met the inclusion criteria and were relevant to the research topic. The results of the study indicate that the implementation of the Problem Based Learning (PBL) model can improve student creativity through problem-solving activities, group discussions, critical thinking, and active idea development. In addition, the PBL model also has a positive impact on learning activeness, communication skills, collaboration, and student learning outcomes. Therefore, the Problem Based Learning (PBL) model can be used as an effective innovative learning model to create active, creative, and meaningful learning in elementary schools.